Implementasi Pembelajaran PAI pada Sekolah Inklusi di Sekolah Inklusi SDN Mentikan 1 Mojokerto - Nihayah, Ishmatun (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
Inclusive schools play a crucial role in accepting all students, including those with special needs (ABK). However, not all inclusive schools successfully implement this concept effectively. This research focuses on SDN Mentikan 1 Mojokerto as an example of an inclusive school, where ABK and regular students learn together with adapted teaching. Specifically, the study explores the planning, implementation, and evaluation of Islamic Education (PAI) learning in the 4th grade. Qualitative methods and a case study approach were utilized, with data collected through interviews, observations, and documentation. The findings indicate that PAI teachers use the same curriculum for both regular and ABK students, implementing full inclusion, clustering, and pull-out models in ABK learning services. The PAI learning process in the 4th grade involves joint participation of ABK and regular students, in accordance with the prepared lesson plans. The evaluation of PAI learning encompasses cognitive, affective, and psychomotor aspects of ABK, using methods such as exams, daily assessments, projects/products, and other evaluations. Remedial actions are taken as needed during the evaluation. This research provides an overview of inclusive PAI at SDN Mentikan 1, highlighting challenges and potential improvements to support the optimal development of all students, especially ABK, in the context of inclusive schooling. The study aims to understand the supporting factors and obstacles in implementing PAI learning in inclusive schools.